Rancang Bangun Mesin Pemanas Akrilik Tipe Turbular Skala Industri Kecil - Noviyanti Nugraha; M. Khenbakti; Rakha Rakha; Teguh Siswanto; Muraz Muraz; Rizkia Munajat (Department of Mechanical Engineering, Universitas Andalas, 2021)
Acrylic is a material that is often used as a substitute for glass because it has the advantage that it is not easily broken and is lighter than glass. One of the processes of making objects made from acrylic is heating. The heating process that has been carried out by small industries is usually acrylic material heated manually by spraying fire from a gas-tube or using a small heater so that the size of acrylic that can be heated is limited, both in terms of length and thickness. The purpose of this research is to design and manufacture an acrylic heating machine that can be used up to a dimension of 600 mm wide and unlimited in length, and can heat up to a thickness of 10 mm with a continuous heating process and is relatively short. The design and manufacture includes the design of the heating system, the selection of the heater to be used, the design and manufacture of the acrylic table, the drive system and the frame. The test parameters include the maximum heating temperature, the acrylic bending temperature and the heating time. The result of the research is an acrylic heating machine that uses three straight turbular heaters with a 300 Watt heater each, capable of heating acrylic with a thickness of up to 10 mm as the initial process for the bending stage, at a heating dimension of 60 cm wide and unlimited in length. The suitable heating temperature for the bending process is 150oC. The average heating time for the thickness 3mm is 91.5 seconds (1.5 minutes), 5mm (2.9 minutes) is 174.2 seconds and 10 mm is 451.3 seconds (7.5 minutes).